An Eight-Year Profile of Children with Influenza A(H1N1) in a Large Hospital in India. (28th September 2021) - Ghosh, Urmi; Bharathy, R V Nirubhan; Prasad, D Jayavelu Hariram; Moorthy, Mahesh; Verghese, Valsan Philip
Abstract:  : As influenza virus A(H1N1) continues to circulate, reports from India have documented mainly respiratory involvement in children. This retrospective chart review of children at a medical college found that from August 2009 to July 2017, 855 children aged 3 months to 15 years had H1N1 influenza of whom 310 (36.3%) were admitted and 29 (9.4% admissions) died. In 2009–12, 76.5% patients presented in August–October but from 2015 to 2017, 89.3% came in January–March. The proportion of under-fives increased from 54.0% in 2009–10 to 77.7% in 2015–17. Among admitted children, 82.6% were under 5 years, 96.1% had respiratory symptoms and 11% had seizures. Six children had encephalopathy of whom four died; two survivors had severe neurological sequelae. Other features included gastroenteritis, otitis media, myositis and hepatitis. Complications included shock (10.7%) and acute respiratory distress syndrome (6.1%). Evidence of bacterial/fungal infection was present in 71 (22.9%). Oxygen was required by 123 children (39.7%), high-dependency/intensive care by 47 (15.2%), 17 (5.5%) received high-flow oxygen and 29 (9.4%) required mechanical ventilation. There were no significantly increased odds of needing intensive care or of dying in children with underlying diseases or among different age groups but those with underlying central nervous system (CNS) diseases had higher odds of needing high-dependency/intensive care [odds ratio (OR) 2.35, p = 0.046]. Significantly, children with CNS symptoms had nearly seven times higher odds of needing mechanical ventilation (OR 6.85, p < 0.001) and over three times higher odds of dying (OR 3.31, p = 0.009).  : Lay summary H1N1 Influenza ("swine flu") emerged as a global pandemic in 2009 and continues to affect children all over the world. This review of records from a medical college hospital in southern India found that 855 children aged 3 months to 15 years came with H1N1 influenza over 8 years from August 2009 to July 2017. In 2009-12, over three-quarters of them presented in the rainy season but from 2015-17, almost 90% came in the winter and spring, suggesting a change in the seasonality of the outbreaks, which could impact the choice of dates for annual influenza vaccination. The proportion under 5 years of age increased from 54% in 2009-10 to 78% in 2015-17, suggesting possible immunity in children exposed to earlier outbreaks. Over a third of the children needed admission of whom almost 40% needed oxygen, one-sixth needed high-dependency/intensive care and 1 in 11 admitted children died, emphasizing the severity of this disease. While most children had respiratory symptoms, all organs of the body were affected; 11% of those admitted had seizures and 6 had encephalitis. Children admitted with central nervous system symptoms had an almost 7-fold higher risk of needing high-dependency/intensive care and an over 3-fold higher risk of dying.